2019
DOI: 10.3390/md17090520
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Acetylation and C-Terminal Amidation of Spirulina platensis-Derived Hexapeptide: Anti-Photoaging Activity and Proteomic Analysis

Abstract: Ultraviolet (UV) irradiation is a potent inducer for skin photoaging. This paper investigated the anti-photoaging effects of the acetylated and amidated hexapeptide (AAH), originally identified from Spirulina platensis, in (Ultraviolet B) UVB-irradiated Human immortalized keratinocytes (Hacats) and mice. The results demonstrated that AAH had much lower toxicity on Hacats than the positive matrixyl (81.52% vs. 5.32%). Moreover, AAH reduced MDA content by 49%; increased SOD, CAT, and GSH-Px activities by 103%, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Intrinsic skin aging is associated with the variation of immune homeostasis and defective barrier function (Zeng et al, 2019), so the immune-microbial alliance is also a vital factor that regulates the intrinsic aging process. We found significant enrichment of Staphylococcus in the youth and middle-aged groups, which would potentially maintain the integrity and healthy status of the skin immune barrier to further affect intrinsic aging.…”
Section: Specific Age-related Microbial Communities and Pathways To Rmentioning
confidence: 99%
“…Intrinsic skin aging is associated with the variation of immune homeostasis and defective barrier function (Zeng et al, 2019), so the immune-microbial alliance is also a vital factor that regulates the intrinsic aging process. We found significant enrichment of Staphylococcus in the youth and middle-aged groups, which would potentially maintain the integrity and healthy status of the skin immune barrier to further affect intrinsic aging.…”
Section: Specific Age-related Microbial Communities and Pathways To Rmentioning
confidence: 99%
“…However, this method of applying oyster may limit the absorption of macromolecular nutrients, such as peptides [24]. At the same time, increasing evidences indicated that topical application of peptides on skin would hydrate the stratum corneum, increase permeability, and enhance drug absorption, eventually shortening the reaction time [24,25]. Thus, it is important to evaluate the ability and efficiency of topical application of peptides from the protein hydrolysates of oyster (Crassostrea hongkongensis) in a UVB-induced photodamaged mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…UVB has been thought to be responsible for the damaging effects in the skin. Therefore, an array of eight UVB lamps (9 W with an emission spectrum between 285 and 350 nm peaked at 310-315 nm, Philips) were used for the construction of the photoaged skin animal model in this study according to previous studies with slight modification [7,25]. Briefly, an array of eight UVB lamps were positioned 16 cm above the floor of a designed apparatus for irradiation.…”
Section: Preparation Of the Photoaged Mouse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…platensis , 25 this hexapeptide decreased the expression of MMP‐1 and MMP‐3. In all analyzes, the action of AAH was superior to that of the positive control with matrixyl, a common active used as anti‐aging agent in cosmetics 27 …”
Section: Anti‐aging Effectmentioning
confidence: 94%